2014
DOI: 10.4018/ijebr.2014070103
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyles and Mobile Services Adoption in China

Abstract: Along with the popularity of mobile devices and advances in wireless technology, mobile services have become more and more prevalent. To the best of knowledge, despite the potential importance of lifestyle, little research has been performed on the effect of various lifestyle factors on mobile services diffusion, particularly in the Chinese context. This study examines the relationship between the lifestyles of Chinese consumers and the adoption of mobile services. Based on a sample of 313 respondents from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, TAM's limitations relative to extensibility and explanation power have been noted [5]. Many researchers have suggested that TAM needs to be extended with additional variables to provide a stronger model [15] [12,24]. Some researchers have also indicated that the major constructs of TAM cannot fully reflect the specific influences of technological and usage-context factors that may alter users' acceptance [29].…”
Section: Technology Diffusion Theorymentioning
confidence: 99%
“…However, TAM's limitations relative to extensibility and explanation power have been noted [5]. Many researchers have suggested that TAM needs to be extended with additional variables to provide a stronger model [15] [12,24]. Some researchers have also indicated that the major constructs of TAM cannot fully reflect the specific influences of technological and usage-context factors that may alter users' acceptance [29].…”
Section: Technology Diffusion Theorymentioning
confidence: 99%
“…It allows users to make video calls, download and transfer files, and use internet-based applications. Smartphones have the potential to enhance the quality of people's life [5,6]. For instance, people can get immediate access to information on a variety of topics through their smartphones.…”
Section: Introductionmentioning
confidence: 99%
“…al Unified Theory of Acceptance and Use of Technology (UTAUT) model. [12] Performance expectancy, effort expectancy, social influence, and facilitating conditions are four influencing constructs of behavioral intention. Hedonic motivation, price value, and habit were later added to the original UTAUT model, which was termed UTAUT2.…”
Section: Hypothesis Development Data Analysis and Resultsmentioning
confidence: 99%